Pengaruh Work-Life Balance dan Stres Kerja terhadap Kinerja Karyawan CreativePlus Production PT Adhi Citra Wiwaha, Jakarta Selatan - Edwina Murdiastuti; Suryanto Sosrowidigdo; Siti Nurjanah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
This study examines work-life balance and workplace stress in relation to employee performance at CreativePlus Production (PT Adhi Citra Wiwaha), a creative content production company based in South Jakarta. Employees in the creative production industry are required to meet deadlines, manage irregular work schedules, and constantly generate new ideas. These conditions can heighten workplace stress and make it difficult to maintain a healthy balance between personal and professional life. Employing a total sampling strategy and a quantitative approach, this study involved all 35 of the organization's employees. Data were collected using Likert-scale questionnaires, and multiple linear regression analysis was performed using SPSS 20. The results indicate that work-life balance has a positive and significant impact on employee performance, whereas work-related stress shows no identifiable effect. Collectively, work stress and work-life balance account for 32% of the variation in employee performance, with other factors contributing the remaining 68%. These findings suggest that work-life balance policies, such as flexible work schedules and mental health services, should be a top priority for organizations in the creative sector to sustain employee performance.